Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.31224/osf.io/ksfbu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impossible by design? Fairness, strategy, and Arrow’s impossibility theorem

Abstract: The design process often requires work by teams, rather than individuals. During teambased design it is likely that situations will arise in which individual members of the team have different opinions, yet a group decision must still be made. Unfortunately, Arrow's Impossibility Theorem indicates that there is no method for aggregating group preferences that will always satisfy a small number of "fair" conditions. This work seeks to identify methods of combining individual preferences that can come close to s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Returning to the context of the early-design stage, design alternatives are often not very well defined and there are doubts about how) to prioritize them (Weingart 2005;Kaldate et al 2006;McComb et al 2017. Although there is a substantial agreement on the design criteria, the selection of design alternatives is generally driven by the different personal experience of designers (Dwarakanath and Wallace 1995).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Returning to the context of the early-design stage, design alternatives are often not very well defined and there are doubts about how) to prioritize them (Weingart 2005;Kaldate et al 2006;McComb et al 2017. Although there is a substantial agreement on the design criteria, the selection of design alternatives is generally driven by the different personal experience of designers (Dwarakanath and Wallace 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Alongside this, a passionate debate on the effects of the Arrow's impossibility theorem in engineering design is still going on (Arrow 2012;Reich 2010;Hazelrigg 1996Hazelrigg , 1999Hazelrigg , 2010Scott and Antonsson 1999;Franssen 2005;Yeo et al 2004;McComb et al 2017). In short, this theorem establishes the impossibility of a generic aggregation model to provide a collective ranking that always satisfies several desirable properties, also known as fairness criteria, i.e., unrestricted domain, non-dictatorship, independence of irrelevant alternatives (IIA), weak monotonicity, and Pareto efficiency (Arrow 2012;Fishburn 1973a;Nisan et al 2007;Saari 2011;Saari and Sieberg 2004;Franssen 2005;Jacobs et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may indicate that optimal team size is task-dependent. In addition, computational work has demonstrated that smaller teams are capable of making decisions that have better axiomatic characteristics [22].…”
Section: Introductionmentioning
confidence: 99%